Gambaran Orientasi Relijius pada Masyarakat di Jakarta - Eko Aditiya Meinarno (Fakultas Psikologi Universitas Pancasila, 2009)
This research is intended to understand description of religious orientation of the community. The basic concept of religious orientation used in this research came from Allport and Ross. The religious orientation is measured using Allport-Ross (AROS) measuring device which had been used by Mohammad and Ginting. It consisting of 20 opinions conducted with a Likert typed scale. There were 157 participants joined in this research. The average of intrinsic religious orientation from the group of participations is 4.48 with SD grade of 0.65 . Furthermore, average value of population is also found to be approximately of 4.38 to 4.59 with 95% l.o.s. If the result of this intrinsic religious orientation average is included in table 2, then the result of its intrinsic religious orientation in considered to be high. Meanwhile, the average of extrinsic religious orientation from the participants is 3.17 to 3.43 with 95% l.o.s. Such outcome if adjusted with table of category then extrinsic religious orientation of the community is rated low.